HEALTHY LIFESTYLE AND MEDICAL CULTURE OF PEOPLE - Turaeva Gulnora Nosirovna; Abdusattarova G.Sh. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The formation of a healthy lifestyle is carried out through information received by a person from the outside, by correcting the lifestyle with the help of feedback, analyzing one's own feelings, the dynamics of objective morphofunctional indicators, interaction with existing valeological knowledge. The formation of a healthy lifestyle is a very long process that can last a lifetime. Feedback caused by changes occurring in the body as a result of following a healthy lifestyle does not work immediately, the positive impact of the transition to a rational lifestyle is sometimes postponed for years.